Exploring Factors Associated With Family Caregivers' Preparedness to Care for an Older Family Member Together With Home Care Nurses: An Analysis in a Swiss Urban Area - Irène Ris; Thomas Volken; Wilfried Schnepp; Romy Mahrer-Imhof (SAGE Publishing, 2022)
Introduction: Home-dwelling older people with chronic diseases often need the support of informal and formal caregivers in order to continue living at home. Family members, however, need to be willing and prepared for caregiving together with home care nurses. Objectives: The purpose of this study was to explore factors associated with family caregivers' preparedness to care for older home-dwelling adults who also receive home care nursing services. Methods: For this cross-sectional correlational study, a structured questionnaire was sent to family caregivers of adults aged 65 years or older receiving services from a community care agency. A total of 243 participants returned the questionnaire, of which 199 could be analyzed. Results: The stepwise backward regression model explained 29.1% of the variance of family caregivers' preparedness. Mutuality was the most strongly associated factor with family caregivers' preparedness whereas professional involvement of family caregiver in care process was important as well. Care intensity showed no significant impact. Conclusion: Nurses should support the whole family emotionally, and appreciate, admire, reinforce, and respect the caregivers' situation. Home care nurses need to invest in helping families to find solutions, to strengthen their relationships between family members and the older person dwelling at home.